DIALEKTIKA NALAR FILOSOFIS DAN DINAMIKA SOSIAL: REAKTUALISASI HUKUM ISLAM DALAM BINGKAI MAQĀṢID AL-SYARĪ’AH - A'isyah A'isyah (UAS PRESS, 2026)
This article develops a philosophical rationale for Islamic law in response to the socio-social changes that plague the contemporary era. As a science that explores the deepest essence of Divine law, Islamic legal philosophy is not merely a tool for theological legitimacy, but also a critical and transformative epistemological instrument. Using the literature study method and the maqāṣid al-syarī’ah approach, this research examines how Islamic legal principles position themselves between the absolute textuality of revelation and relative sociological reality. The study positions Islamic law as a dialectical product of the philosophy of al-tashri’ and the philosophy of al-syarī’ah that gives rise to legal flexibility, namely law based on benefit, maṣlaḥah. The author argues that the reactualization (reduction of long-term conditions) of Islamic law can only occur through philosophical ijtihād that is able to combine transcendental values ​​(the supernatural, beyond reason, beyond reason) with empirical human needs. The article emphasizes that true justice in Islamic law is dynamic, so it prides itself on the renewal of schools of thought to ensure that the law of ṣāliḥ li kulli zamān wa makān is homogeneous.